Why Wall? A Kleinian Reading of the Israeli-Palestinian Resistance to Politics (Konturen, 2012)
The present work explores the separation barriers built by the Israeli government and military as products and producers of asymmetries of power between Israelis and Palestinians; and, at the same time, as products and producers of discourses that are characterized by the naturalization of evil. In such discourses, evil is singularized as a unique cultural property of the national adversary; violence and aggression on the part of the adversary are perceived as a sign of a primitive morality, detached from political and historical circumstances; and violence of each party is justified as a defensive war on the “evil” other. A return to Melanie Klein allows to trace these dynamics, and to raise fundamental questions on the role of the cultural analyst.